Bioethics as a philosophical task - Ferrer, Jorge José (Acta Bioethica, 2009)
This article examines the epistemological statute of bioethics as an academic discipline. The author claims that the epistemological statute of a dialogue determines the fundamental question that is raised and the answer that is sought, essential points of discourse. In the case of bioethics, the fundamental question is of a moral nature. Therefore, bioethics is an ethical discipline that has its epistemological roots in philosophy. The author also defends the concept of applied ethics. Finally, he suggests that bioethical methods, above all especially what is realized in our latitudes, should adopt the Hermeneutic Circle as the methodology for its philosophizing.